Characteristics, Biological Properties and Analytical Methods of Piperine: A Review - Quijia, Christian Rafael [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2019)
Piperine (PIP) is a natural alkaloid isolated from Piper longum L. that presents antioxidant, anticonvulsant, antimicrobial, neuroprotective, larvicidal, antiparasitic, anticancer effect and other pharmacological properties. However, the low aqueous solubility is the main barrier to its development from the laboratory to the clinic as a drug. Several strategies have been used to overcome this obstacle, like the incorporation of PIP into different drug delivery systems turned out to be highly efficient. In addition, several methods for the quantitative and qualitative analysis of PIP in various raw materials, including biological fluids (plasma, urine, metabolites, brain), plants and drug delivery systems, were investigated. Most recently high-performance liquid chromatography was used together with several detectors for this purpose. Therefore, this review presents a summary of characteristics chemical and biological properties of PIP as well as several techniques and analytical methods to optimize the analytical signal, increase sensitivity, selectivity and reduce the effects of interference for this drug.
Keywords: High-performance liquid chromatography; Piper longumL; piperine